Formal methods of parallel software design automation - Doroshenko, A.Yu.; Яценко, О.А. (Reports of the National Academy of Sciences of Ukraine, 2020)
Formal methods and software tools of automated design and synthesis of parallel programs are proposed. The developed facilities use the language based on the Glushkov system of algorithmic algebras intended for a highlevel and natural linguistic representation of algorithms and apply rewriting rules technique to transform programs. The tools also use the method of syntactically correct algorithm scheme design which eliminates syntax errors during the construction of algorithms and programs. The approach is illustrated on developing the parallel N-body simulation program for the executing on a graphics processing unit.